Gas sensor devices based on metal oxide foams
By adopting a three-dimensional connected metal oxide foam structure and a gas sensing device that extends the channel hole, the problem of existing equipment being difficult to monitor low concentrations of toxic gases is solved, and gas sensing effects with higher sensitivity and faster response time are achieved.
Patent Information
- Application Number
- JP2021557378
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-26
- Filing Date
- 2020-03-26
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2040-03-26
AI Technical Summary
Existing gas sensing devices are difficult to effectively monitor low concentrations of toxic gases and have a long response time, which cannot meet the industrial and private sector needs for high sensitivity and rapid response.
Using three-dimensionally connected metal oxide foam structures and gas sensing devices extending channel holes, a platinum electrode and a manganese oxide heater are printed on a low-temperature co-fired porcelain substrate and the prepared metal oxide foam induction material is connected to the silver paste to form an induction layer with a larger surface area to improve sensitivity and response speed.
Higher sensitivity and faster response times to low concentrations of toxic gases such as ethanol and carbon monoxide are achieved, significantly improving gas sensing performance.
Smart Images

Figure 0007655856000001 
Figure 0007655856000002 
Figure 0007655856000003
Abstract
Description
[Technical field]
[0001] explanation CROSS-REFERENCE TO RELATED APPLICATIONS This patent application claims the benefit of U.S. Patent Application No. 62 / 824,276, filed March 26, 2019, the contents of which are incorporated by reference along with all other references cited in this application.
[0002] 2. Background of the Invention The present invention relates to the field of gas sensing device technology. More specifically, the present invention is to develop a highly sensitive gas detection device using metal oxide foam for effectively monitoring various toxic gases by suitable gas sensors, which can detect the presence of toxic gases from very low to high particle concentrations with higher sensitivity and shorter detection time. [Background technology]
[0003] Technical difficulties arise because most toxic gases exist in relatively low concentrations. It is very important to select an appropriate sensing material that exhibits accurate sensitivity response to low concentrations of the target gas. It is also important to use a gas sensor device with a shorter sensing time so that the target gas can enter and exit as quickly as possible. Summary of the Invention [Problem to be solved by the invention]
[0004] There are various industrial and private sectors that desperately require advanced gas detection technology. For example, dramatic advances in modern technology have created a large number of toxic gases that are of great concern for accidental release, and these gases can have serious effects on the environment and on both human and animal health. Additionally, new regulations in the United States require that all new buildings should be equipped with carbon monoxide detectors to prevent fire hazards.
[0005] Thus, there is a need for improved gas sensing device techniques and materials. [Means for solving the problem]
[0006] SUMMARY OF THE PRESENT APPLICATION A new gas sensing device is fabricated with a large surface area three-dimensionally connected metal oxide foam structure and elongated channel holes within the three-dimensional porous structure for gas sensing applications, which increases the surface area of the sensing layer and promotes sensitivity and sensor response. The gas sensor device is fabricated with platinum electrodes and Oxidation The device includes a fabricated metal oxide foam sensing material attached via silver paste to a ruthenium heater. This device can provide improved gas sensing performance with improved sensitivity and response time (e.g., faster gas in / out). The gas sensor including the metal oxide foam sensing material shows higher sensitivity to toxic gases such as ethanol and carbon monoxide. This is due to the larger surface area achieved from the porous three-dimensional structure that provides increased chemical reaction fields, and the larger porous channels that allow gas to easily pass through and shorten the gas diffusion reaction path.
[0007] The method is explicitly described based on the results of tin oxide gas sensing materials, but can be extended to many other metal oxides, and involves the fabrication of metal oxide foams with pore sizes ranging from hundreds of nanometers to tens of micrometers, and applying these as sensing materials for gas sensor applications. The fabricated metal oxide foams react with toxic gases over their extended surface layer when exposed to a target gas.
[0008] A new method for fabricating three-dimensional metal oxide foams (e.g., tin oxide and copper oxide foams, for example) for use as advanced gas sensing materials. The method consists of fabricating tin oxide foam with pore sizes ranging from hundreds of nanometers to a few micrometers for use as a gas sensing material, and then patterning two electrode pads 200 microns apart on the metal oxide foam by a lift-off process using a shadow mask.
[0009] Gas sensors containing porous tin oxide foams show higher sensitivity to toxic gases such as ethanol and carbon monoxide due to the larger surface area achieved from the porous three-dimensional structure that provides increased chemical reaction sites, and larger porous channels that allow gases to easily pass through and shorten the gas diffusion reaction path.
[0010] Tin oxide is a commonly used gas sensing material that is applicable to n-type or p-type gas sensors depending on its crystal structure. This patent details the fabrication of tin oxide and other metal oxide foams using a novel method that combines slurry formation and powder sintering to provide gas sensing materials of improved sensitivity. Tin oxide foams fabricated using the method detailed in this patent exhibited different morphological characteristics depending on key processing parameters such as sintering temperature, sintering time, and amount of powder added. Scanning electron microscope images identified a two-stage pore structure within the tin oxide foam that included an array of 5.3-10.7 micron pores, and smaller secondary pores several microns in diameter on the wall surface. Gas sensing performance for the synthesized tin oxide foam in a larger experimental chamber showed a sensitivity of 13.1, a response time of 192 seconds, and a recovery time of 160 seconds for ethanol gas at 600 parts per million at 300 degrees Celsius, and 35.9 seconds, 39 seconds, and 27 seconds, respectively, for carbon monoxide at 5000 parts per million at 200 degrees Celsius, which is an excellent sensing result considering that the samples fabricated according to the current patent were catalyst-free.
[0011] Furthermore, freeze-cast copper oxide foam showed a steady increase in sensitivity of copper oxide foam with increasing carbon monoxide gas concentration at low carbon monoxide concentrations of 1000 ppm to 5000 ppm at 300 degrees Celsius, confirming that the metal oxide sensor structure is beneficial for sensing toxic gases such as carbon monoxide due to its enhanced sensing surface area. A metal oxide foam gas sensor device was fabricated such that platinum electrodes and ruthenium oxide heaters were printed onto a low temperature co-fired ceramic (LTCC) substrate before the metal oxide foam sensor was attached on top of the heater and electrode using Ag paste. This sensor device is a direct replacement for existing sensing material components.
[0012] In implementation, the gas sensor device includes a metal oxide foam sensing material that is coupled via silver paste to a platinum electrode and a ruthenium heater printed on the LTCC. The electrode pattern may include two electrode pads of a suitable metal, such as platinum, spaced a few hundred micrometers apart, using a lift-off process and a shadow mask, for use as electrodes in the attached metal oxide foam sensor.
[0013] The metal oxide foam has a porosity between about 55 percent and about 90 percent and is the gas sensing material in the sensor device that reacts with specific target (e.g., toxic) gases such as ethanol, carbon monoxide, oxygen, nitric oxide, hydrogen, toluene, and other gases. The sensing material includes at least one of tin oxide foam or tin oxide foam with at least one of palladium, gold, silver, or platinum catalyst in the range of 0.1 weight percent to 3 weight percent.
[0014] The sensing material is a metal oxide foam, such as a semiconductor type sensor. The porous sensing material can be either one or a combination of tin oxide (SnO or SnO2), zinc oxide (ZnO), indium oxide (In2O3), tungsten oxide (WO3), titanium oxide (TiO2), nickel oxide (NiO), copper oxide (CuO), cobalt oxide (Co3O4), chromium oxide (Cr2O3), and iron oxide (Fe2O3), or other metal oxides with similar properties.
[0015] The manufacturing process for forming the porous metal oxide foam sensing material can be at least one of, or a combination of, freeze casting, space holder, or dealloying. The manufacturing process for forming the porous metal oxide foam sensing material may include a freeze casting method followed by a powder slurry preparation and sintering process, in which a water-based or camphene-based oxide powder slurry is frozen and dried at low temperature to form a green body, and then sintered at high temperature to form a three-dimensionally connected solid porous structure.
[0016] The sensing material may be a semiconductor type sensor using metal oxide, and the porous sensing material may be fabricated via at least one of thermal oxidation or anodization processes on the surface of a metal foam (e.g., Sn, Zn, In, W, Ti, Ni, Cu, Co, Cr, or Fe) fabricated via at least one of freeze casting, space holder, or dealloying. The metal oxide sensing material may be configured in the form of at least one of a thin layer of oxide or nanoneedle oxide on the surface of the prepared metal foam.
[0017] Tin oxide foams can be fabricated with the addition of sintering aids such as Li2O, CuO, MnO2, ZnO, or La2O3, or the like, in a composition range of about 0.1 weight percent to about 3 weight percent to aid in densification by forming a liquid phase during sintering of the tin oxide green body.
[0018] In practice, a method for producing metal oxide foam using a freeze casting process includes: placing a rectangular insulating silicone mold on a copper or aluminum block immersed in liquid nitrogen, controlled with a thermocouple and temperature controller, and pouring a metal oxide slurry containing at least one of deionized water, a dispersant, a binder, a metal or metal oxide powder, and a sintering aid into the mold; freezing the slurry such that ice dendrites form and grow in the slurry, with the metal or metal oxide particles gathering between the growing ice crystals; forming a green body metal (oxide) foam by drying the ice crystals of the frozen sample at a sufficiently low temperature, between about -10 degrees Celsius and about -80 degrees Celsius, and at reduced pressure, leaving the pores in their original locations; sintering the porous green body at a sufficiently high temperature, between about 800 degrees Celsius and about 1700 degrees Celsius, in a controlled furnace under air or argon atmosphere, to form a three-dimensionally connected porous metal oxide foam with sufficient integrity; forming the metal oxide foam into a mold that is connected to a porous metal oxide powder; Oxidation Machined into a rectangular shape that is directly applicable as the sensing material in a gas sensor with a ruthenium heater and an underlying platinum electrode.
[0019] In practice, the method of applying the fabricated metal oxide foam for a gas sensor includes a patterning process to attach electrode pads to the metal oxide foam sensing material in a suitable pattern. The gas sensor is fabricated using platinum electrodes and Oxidation It may include a metal oxide foam sensing material coupled via silver paste to a ruthenium heater.
[0020] Other objects, features and advantages of the present invention will become apparent from a consideration of the following detailed description and the accompanying drawings, in which like reference designations represent respective like structures throughout. [Brief description of the drawings]
[0021] [Figure 1A] FIG. 1 shows a schematic diagram of a general sensing mechanism for n-type and p-type semiconductor sensors. [Figure 1B] FIG. 1 shows a schematic diagram of a general sensing mechanism for n-type and p-type semiconductor sensors. [Figure 1C] FIG. 1 shows a schematic diagram of a general sensing mechanism for n-type and p-type semiconductor sensors. [Figure 2A] 1 is a photograph of a tin oxide foam sample before and after sintering. [Figure 2B] 1 is a photograph of a tin oxide foam sample before and after sintering. [Figure 3A] FIG. 1 shows X-ray diffraction patterns for tin oxide foam samples heat treated at various temperatures. [Figure 3B] FIG. 2 shows the tin K-edge near-edge X-ray absorption structure spectrum for tin oxide foam. [Figure 3C] FIG. 1 shows X-ray photoelectron spectroscopy measurements on tin oxide. [Figure 3D] FIG. 1 illustrates the bond energy position for tin oxide. [Figure 4A] 1A-1C are scanning electron micrographs of radial and fracture surfaces for tin oxide foam. [Figure 4B] 1A-1C are scanning electron micrographs of radial and fracture surfaces for tin oxide foam. [Figure 4C] 1A-1C are scanning electron micrographs of radial and fracture surfaces for tin oxide foam. [Figure 4D] 1A-1C are scanning electron micrographs of radial and fracture surfaces for tin oxide foam. [Figure 4E] 1A-1C are scanning electron micrographs of radial and fracture surfaces for tin oxide foam. [Figure 4F] 1A-1C are scanning electron micrographs of radial and fracture surfaces for tin oxide foam. [Figure 4G] 1A-1C are scanning electron micrographs of radial and fracture surfaces for tin oxide foam. [Figure 4H] 1A-1C are scanning electron micrographs of radial and fracture surfaces for tin oxide foam. [Figure 5A] FIG. 5 shows the change in electrical resistance (gas sensitivity) of tin oxide foam for different exposure times to various concentrations of ethanol gas (FIG. 5A) and carbon monoxide gas (FIG. 5B). [Figure 5B] FIG. 5 shows the change in electrical resistance (gas sensitivity) of tin oxide foam for different exposure times to various concentrations of ethanol gas (FIG. 5A) and carbon monoxide gas (FIG. 5B). [Figure 6A] FIG. 1 compares the sensing response for tin oxide foam in ethanol and carbon monoxide gases. [Figure 6B] FIG. 1 compares the sensing response for tin oxide foam in ethanol and carbon monoxide gases. [Figure 7A] FIG. 1 compares the change in electrical resistance and gas sensitivity of tin oxide foam with and without palladium loading at 200 degrees Celsius. [Figure 7B] FIG. 1 compares the change in electrical resistance and gas sensitivity of tin oxide foam with and without palladium loading at 200 degrees Celsius. [Figure 8] FIG. 1 shows a sensitivity comparison between tin oxide foam with and without palladium loading at various temperatures. [Figure 9A] FIG. 1 shows the change in electrical resistance and gas sensitivity of tin oxide foam with catalytic palladium loading at low concentrations and 200 degrees Celsius. [Figure 9B] FIG. 1 shows the change in electrical resistance and gas sensitivity of tin oxide foam with catalytic palladium loading at low concentrations and 200 degrees Celsius. [Figure 10A] FIG. 1 shows the change in electrical resistance and gas sensing mechanism of copper oxide foam under various carbon monoxide concentrations, and the sensing response. [Figure 10B] FIG. 1 shows the change in electrical resistance and gas sensing mechanism of copper oxide foam under various carbon monoxide concentrations, and the sensing response. [Figure 10C]FIG. 1 illustrates the change in electrical resistance and gas sensing mechanism of copper oxide foam under various carbon monoxide concentrations, and the sensing response. [Figure 11A] FIG. 1 shows a schematic process flow for fabricating a metal oxide foam sensor device with platinum electrodes and ruthenium oxide heater printed on an LTCC substrate. [Figure 11B] FIG. 1 shows a schematic process flow for fabricating a metal oxide foam sensor device with platinum electrodes and ruthenium oxide heater printed on an LTCC substrate. [Figure 11C] FIG. 1 shows a schematic process flow for fabricating a metal oxide foam sensor device with platinum electrodes and ruthenium oxide heater printed on an LTCC substrate. [Figure 11D] FIG. 1 shows a schematic process flow for fabricating a metal oxide foam sensor device with platinum electrodes and ruthenium oxide heater printed on an LTCC substrate. [Figure 11E] FIG. 1 shows a schematic process flow for fabricating a metal oxide foam sensor device with platinum electrodes and ruthenium oxide heater printed on an LTCC substrate. [Figure 11F] FIG. 1 shows a schematic process flow for fabricating a metal oxide foam sensor device with platinum electrodes and ruthenium oxide heater printed on an LTCC substrate. [Figure 11G] FIG. 1 shows a schematic process flow for fabricating a metal oxide foam sensor device with platinum electrodes and ruthenium oxide heater printed on an LTCC substrate. [Figure 12] FIG. 1 illustrates a gas sensor product comprising a tin oxide foam sensor device that replaces an existing larger commercially available sensing module. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Detailed Description of the Invention Metal oxide gas sensors are one of the most commonly used sensing devices for commercial gas sensing applications. They are based on the principle of a change in electrical resistance (or conductivity) due to gas absorption on the surface of a sensing material exposed to a target gas.
[0023] A common sensing material is tin oxide (SnO or SnO 2 ) and zinc oxide (ZnO), both of which exhibit excellent semiconducting sensing behavior. Copper oxide (CuO), nickel oxide (NiO), titanium oxide (TiO 2 ), tungsten trioxide (WO 3 ), indium oxide (In 2 O 3 ), and iron oxide (Fe 2 O 3 Other metal oxide semiconductors such as ZnO, ZnSe, and ZnSe are also being used for new chemical or resistive functionalities or combinations due to their good response and selectivity to ambient conditions, as well as the ease of material synthesis and sensing device fabrication.
[0024] Controlling the (surface) morphology of gas-sensing materials is an effective way to enhance the sensing properties. It is important to understand the microstructure of the sensing material because the particle size, morphology, surface condition, and accessible surface area all play important roles in the gas sensing performance. In general, the adsorption or desorption process occurs on the surface of the sensing layer and determines the sensor response.
[0025] Accordingly, in recent years, there has been a dramatic increase in research and development into the design of gas-sensing materials, including nanowires, nanoparticles, nanorods, nanotubes, and hollow spheres. However, these efforts have not provided sufficient solutions, and the need for improved gas sensitivity remains.
[0026] The new gas sensing device is based on a new metal oxide foam material with enhanced surface area and higher gas permeability. The three-dimensional pore structure on the surface of the metal oxide foam used in this device can improve the desorption process of the surface sensing layer, thus improving the sensitivity and response time to the target gas.
[0027] Fabricating the porous structure includes the following steps: (a) freezing a metal or metal oxide slurry together with a metal or metal oxide powder and a sintering aid powder (e.g., copper oxide) in a silicone mold in contact with the cold surface of a copper rod; (b) sublimating the frozen slurry under reduced pressure and low temperature to form a porous green body; (c) sintering the porous green body to obtain a three-dimensionally connected porous metal oxide foam; (d) cutting the porous metal oxide foam into 10 millimeter by 20 millimeter panels to be used as sensing materials; and (e) patterning platinum electrode pads on the porous foam at 200 micron intervals using a lift-off process and a shadow mask.
[0028] The porous structure of tin oxide foam used as the sensing material of the gas sensor can provide a larger surface area (e.g., compared to non-foam materials) with directional channel pores, which can help the target toxic gases to flow through. This two-stage pore structure with a large surface area can sense toxic gases with improved sensitivity when exposed to ethanol, carbon monoxide, and others, as shown diagrammatically in FIG. 1.
[0029] A variety of oxide-based gas-sensitive semiconductor material foams can be fabricated into three-dimensional porous structures, all prepared from starting powder forms. For example, these foams can be made from tin oxide (SnO or SnO 2 ), zinc oxide (ZnO), indium oxide (In 2 O 3 ), tungsten oxide (WO 3 ), titanium dioxide (TiO 2), Nickel oxide (NiO), Copper oxide (CuO), Cobalt oxide (Co 3 O 4 ), chromium oxide (Cr 2 O 3 ), and iron oxide (Fe 2 O 3 ). The initial materials may also be their corresponding metal powders, since frozen and dried green bodies made of metal powders may be sintered at high temperatures in a hydrogen atmosphere rather than in an air atmosphere for reduction. Tin oxide and copper foams are the specific examples discussed in this patent, but other metal oxide materials may be similarly applied for use as gas sensing materials, as long as they are semiconducting materials with wide band gaps, high conductivity, and good stability, as discussed above.
[0030] Porous metal oxide foams are three-dimensionally connected porous structures with pore sizes ranging from hundreds of nanometers to tens of microns, with the pores spanning three dimensions. Three-dimensional metal oxide foams are fabricated based on a combination of slurry foaming and powder sintering, a relatively simple and low-cost processing method suitable for fabricating small or large scale structures. However, the manufacturing process of porous metal oxide foams is not limited to this powder processing, and other methods may be utilized to fabricate metal oxide foam structures applied as sensor devices with improved sensitivity.
[0031] To produce tin oxide foam, sintering aids such as copper oxide can aid the densification process by forming a sintering liquid phase. Porous tin oxide with sintering aids (e.g., copper oxide) can achieve uniform volumetric shrinkage of the foam in the sintering process so that cracks do not occur (Figure 2). We believe that the shrinkage is nearly isotropic and residual stress due to shrinkage is minimal. Tin oxide is known to be difficult to densify during sintering because the mass transfer mechanism of tin oxide is rather complex and controlled by surface diffusion at low temperatures (e.g., temperatures below 1000 degrees Celsius) and by evaporation-condensation at high temperatures (e.g., temperatures above 1300 degrees Celsius). Uniform densification is difficult to achieve when either of these mechanisms dominate. However, sintering aids (e.g., copper oxide) play an important role in promoting bulk or grain boundary diffusion or forming a liquid phase or both during sintering of tin oxide.
[0032] Based on the described fabrication of tin oxide foam, there can be relatively simple modifications to produce numerous types of porous metal oxide foams used as three-dimensional gas sensing materials, such as titanium oxide, nickel oxide, cobalt oxide, zinc oxide, and others.
[0033] This application describes some examples of implementations with specific scales, dimensions, and values. They are not intended to be exhaustive or to limit the invention to exact variations from those described. Values, percentages, times, and temperatures are approximate. These values may vary, for example, due to manufacturing variations in dimensions or starting powder chemistry or tolerances or other factors. For example, depending on the tightness of manufacturing and dimensional tolerances, values may vary by plus or minus 5 percent, plus or minus 10 percent, plus or minus 15 percent, or plus or minus 20 percent.
[0034] Additionally, the values are for a particular implementation and other implementations may have different values, such as a certain value being larger for a scaled-up size process or product, or smaller for a scaled-down product. An apparatus, device, or process may be made proportionally larger or smaller by proportionally adjusting the relevant dimensions (e.g., maintaining the same or approximately the same ratio between different dimensions). In various implementations, the values may be the same as a given value, approximately the same as a given value, greater than or equal to a given value, or less than or equal to a given value, or any combination thereof.
[0035] The process of manufacturing porous metal oxide foams for use as gas sensing materials may include the following steps: 1. Placing a silicone mold on a copper rod or similar highly thermally conductive material that is immersed in liquid nitrogen, and pouring a metal oxide slurry, with powder sizes typically in the range of tens or hundreds of nanometers, into the mold along with a binder and one or more sintering aids.
[0036] 2. Freezing the prepared metal oxide slurry, whereby the metal oxide particles become stacked and physically attached between the growing ice crystals.
[0037] 3. Forming a porous green body by drying the ice crystals from the frozen slurry at a temperature and vacuum low enough to leave pores in the structure and maintain physical attachment.
[0038] 4. Consolidating the metal oxide foam having tightly connected pores by debinding, and sintering the porous green body at a sufficiently high temperature in an air atmosphere.
[0039] 5. Cutting the porous metal oxide foam into a 10 mm by 20 mm rectangular form for use as a sensing material in a gas sensor.
[0040] 6. Patterning two platinum electrode pads with 200 micron spacing on the porous foam by a lift-off process using a shadow mask.
[0041] Illustrative embodiment 1: Preparation of tin oxide foam Tin oxide powder (e.g., 15.5 grams) was suspended in 20 milliliters of deionized water solution containing polyvinyl alcohol binder, and a sintering aid (e.g., copper oxide (CuO) powder, less than 3 weight percent) was added to improve tin oxide powder densification. The slurry was dispersed by manual stirring for 30 minutes and then sonicated for 1 hour. The stirring process was repeated twice to ensure sufficient particle dispersion.
[0042] The slurry was then cooled to a few degrees above the freezing point of water and poured into a cylindrical mold made of insulated polytetrafluoroethylene (PTFE), Teflon, or silicone, or a combination, over a copper rod, which was cooled using liquid nitrogen controlled by a thermocouple and temperature controller.
[0043] Once the freezing process was complete, the frozen tin oxide green foam samples were removed from the molds and cooled for 10 min. -2 The samples were dried at -80°C in a freeze dryer under 1000 torr of residual stress for 48 hours and then heat treated in two separate steps: the first treatment was at 300°C for 3 hours to remove the binder, followed by sintering at 1150°C in a box furnace in air for 10 hours.
[0044] Exemplary embodiment 2: Preparing the sensing device To fabricate a highly sensitive gas sensing device, two platinum electrode pads and a ruthenium oxide heater were printed on a low-temperature co-fired ceramic (LTCC) substrate. Ruthenium oxide (RuO 2) heater layer was formed, and then two platinum electrodes were patterned with a 200 micron gap using a lift-off process and a shadow mask. Then, the gas sensitivity was measured at different ethanol gas concentrations from 20 to 60 parts per million at 300 degrees Celsius. For carbon monoxide gas sensing performance, the sensor response was measured for low concentrations of 100 to 500 parts per million and high concentrations of 1000 to 5000 parts per million at 200 to 300 degrees Celsius. During the measurements, the gas concentration was kept in equilibrium and controlled by a mass flow controller (MFC). The sensor electrical resistance was continuously measured at a constant microangstrom while gas was injected into the sensor chamber.
[0045] 1A-1C show schematics of the general sensing mechanism for n-type and p-type semiconductor sensors, and in particular for the exemplary tin oxide foam sensor shown in this patent.
[0046] Figures 2A-B show photographs of a representative tin oxide foam before and after sintering in air. The foam reduces from a diameter of 45 millimeters and a height of 16 millimeters (Figure 2A, left) to a diameter of 31 millimeters and a height of 11 millimeters (Figure 2B, right), resulting in a volumetric shrinkage of 67 percent with radial and height shrinkage of nearly 31 percent. The sample maintains its integrity after sintering without cracks or distortion. Thus, the shrinkage appears to be nearly isotropic, suggesting minimal residual stress due to shrinkage.
[0047] FIG. 3A shows the X-ray diffraction patterns of four tin oxide foam samples heat treated at 1050°C, 1100°C, 1150°C, and 1250°C, respectively, for 10 hours. There are no significant differences between the X-ray diffraction (XRD) peaks of the four foam samples, and they all match typical tin oxide (SnO 2 ) peaks are shown.
[0048] FIG. 3B shows commercially available tin monoxide (SnO) and tin dioxide (SnO 2 3C) shows the tin K-edge near-edge X-ray absorption structure spectrum for tin oxide foam heat treated at 1150 degrees Celsius for 10 hours compared to the powder survey, and (Figure 3D) the 3D X-ray photoelectron spectroscopy spectrum of the 3D metallic tin for tin oxide foam after sintering in air at 1150 degrees Celsius for 10 hours.
[0049] The oxidation state of tin in the foams was determined by obtaining tin (Sn) K-edge XANES (X-ray absorption near edge structure) spectra (Figure 3B) and comparing the absorption edge position of the foams with that of commercial tin oxides (e.g., SnO and SnO 2 The average tin valency was 3.36 in the foam samples, and the tin oxidation state throughout the foam samples was predominantly tin dioxide (SnO 2 )
[0050] FIG. 3C shows X-ray photoelectron spectroscopy (XPS) measurements performed to investigate the chemical state of the tin oxide foam surface. FIG. 3D shows the binding energy position of the tin 3d peak (3d 5 / 2 About 486.3 electron volts and 3d 3 / 2 The results show that the surface tension of the foam is also composed of tin oxide (SnO), indicating that the surface tension of the foam is also composed of tin oxide (SnO).
[0051] 4A-H show scanning electron micrographs of radial and fractured sections for tin oxide foams sintered at various temperatures resulting in a dual-stage pore structure: 10 hours, (FIGS. 4A and 4E) 1050 degrees Celsius, (FIGS. 4B and 4F) 1100 degrees Celsius, (FIGS. 4C and 4G) 1150 degrees Celsius, and (FIGS. 4D and 4H) 1250 degrees Celsius. Arrows in the top view images (e.g., FIGS. 4A-4D) indicate junctions typical of metal oxide powder sintering processes, while arrows in the fractured sections (e.g., FIGS. 4E-4H) indicate secondary dendrites on the wall struts.
[0052] Figures 5A-5B show the change in electrical resistance (gas sensitivity) of tin oxide foam heat treated at 1150 degrees Celsius for 10 hours for different exposure times to various concentrations of (Figure 5A) ethanol gas and (Figure 5B) carbon monoxide gas. The change in electrical resistance confirms that the tin oxide foam samples can perform significantly in gas sensing devices.
[0053] FIG. 5A shows the resistance change or sensitivity of a tin oxide foam sample versus measurement time during exposure to ethanol gas having concentrations between 20 and 60 parts per million. The tin oxide foam responded with a substantial increase in electrical resistance with increasing exposure to ethanol gas (e.g., FIG. 5A, striped columns), and the resistance returned to a stable value when the gas was replaced by pure air (e.g., FIG. 5A, white columns). The tin oxide foam exhibited a response of 13.1 (unitless) for 60 parts per million ethanol gas at 300 degrees Celsius, which is very impressive considering that no catalyst was added. Thus, the tin oxide foam synthesized by the method embodied in this patent is suitable as an ethanol gas sensing material.
[0054] FIG. 5B shows the resistance change or sensitivity of tin oxide foam versus measurement time during exposure to carbon monoxide gas having concentrations of 1000 to 5000 parts per million. The tin oxide foam sensor exhibited a response value of 35.9 (unitless) at 5000 parts per million monoxide gas at 200 degrees Celsius without catalyst addition. The sensitivity increased approximately linearly with increasing monoxide concentration. Thus, the tin oxide foam synthesized by the method embodied in this patent is suitable as a carbon monoxide gas sensing material.
[0055] 6A-6B compare the sensing response of tin oxide foam with that of: (FIG. 6A) NiO nanoparticles and tin oxide SnO as functional groups of ethanol concentration at 300 degrees Celsius; 2 nanowires, and (FIG. 6B) tin oxide thin film samples at various temperatures under carbon monoxide gas. The tin oxide foam samples successfully sense carbon monoxide gas at substantially lower concentrations than the conventional tin oxide thin films.
[0056] The three-dimensional tin oxide foam sensing material fabricated as detailed in Examples 1 and 2 achieved high sensitivity compared to other sensing materials without the need for additional catalysts, as shown in FIG. 6A. In particular, FIG. 6B shows that the three-dimensional tin oxide foam fabricated as detailed in this patent detected carbon monoxide gas at very low concentrations, which could not be achieved by conventional tin oxide thin films. Thus, the unique three-dimensional porous tin oxide structure allows easy diffusion of toxic gases through the channel-like pores and increases the surface area by adjusting the key processing parameters such as sintering conditions and powder content. Thus, the tailored pore structure in the tin oxide foam facilitates gas diffusion by shortening the reaction path.
[0057] 7A-7B show (FIG. 7A) the change in electrical resistance (gas sensitivity) of tin oxide foam with 3.0 weight percent palladium added as a catalyst for various carbon monoxide gas concentrations compared to the change in electrical resistance (gas sensitivity) of tin oxide foam without palladium added, and (FIG. 7B) a sensitivity comparison between tin oxide foam with and without palladium added as a functional group for carbon monoxide gas concentration at 200 degrees Celsius.
[0058] The addition of small amounts of catalysts such as palladium, platinum, or others can certainly improve the sensitivity of metal oxide foam sensors. Figure 7A shows a comparison of the electrical resistance change (gas sensitivity) of tin oxide foam with and without 3.0 weight percent palladium as a catalyst addition for various carbon monoxide gas concentrations. As shown in Figure 7B, the sensitivity of the tin oxide foam sensor with palladium addition is significantly higher than that of the tin oxide foam sensor without palladium over the entire range of carbon monoxide gas concentrations at 200 degrees Celsius. Furthermore, the sensitivity of the tin oxide foam sensor with palladium is higher than that of the tin oxide foam sensor without palladium over the entire temperature range from 200 degrees Celsius to 300 degrees Celsius (Figure 8).
[0059] Figure 8 shows a sensitivity comparison between palladium-doped and undoped tin oxide foam at various temperatures for a carbon monoxide gas concentration of 4500 parts per million (ppm). The palladium-doped tin oxide foam shows significantly higher sensitivity over the entire temperature range between 200 and 300 degrees Celsius.
[0060] 9A-9B show (FIG. 9A) the change in electrical resistance (gas sensitivity) of tin oxide foam with palladium added as a catalyst at low concentrations (100-500 ppm) of carbon monoxide gas at 200 degrees Celsius, and (FIG. 9B) the sensitivity of tin oxide foam with palladium added as a function of carbon monoxide gas concentrations between 100 and 500 parts per million (ppm) at 200 degrees Celsius.
[0061] In particular, the addition of palladium is beneficial for the low concentration range of carbon monoxide gas. Figure 9A shows the change in electrical resistance (gas sensitivity) of tin oxide foam with palladium added as a catalyst at low carbon monoxide gas concentrations (e.g., 100-500 parts per million) at 200 degrees Celsius. In such a low concentration range of carbon monoxide gas, the sensitivity of the tin oxide foam with palladium added increases steadily with increasing carbon monoxide gas concentration between 100-500 parts per million at 200 degrees Celsius.
[0062] 10A-10C show (FIG. 10A) the change in electrical resistance (gas sensitivity) of copper oxide foam at carbon monoxide concentrations between 1000 parts per million (ppm) and 5000 parts per million at 300 degrees Celsius, (FIG. 10B) an outline of its mechanism of operation, and (FIG. 10C) the sensitivity (response) of copper oxide foam as a function of carbon monoxide gas concentrations between 1000 and 5000 parts per million at 300 degrees Celsius.
[0063] For the fabrication of metal foam oxide gas sensing devices, not only tin oxide foam sensors are applicable, but also other metal oxide foam sensors. Figure 10A shows the change in electrical resistance (gas sensitivity) of freeze-cast copper oxide foam at relatively low carbon monoxide concentrations of 1000 parts per million to 5000 parts per million at 300 degrees Celsius, and Figure 10C shows the sensitivity of copper oxide foam steadily increasing with increasing carbon monoxide gas concentrations between 1000 and 5000 parts per million at 300 degrees Celsius, confirming that the metal oxide sensor structure is beneficial for detecting toxic gases such as carbon monoxide due to its enhanced sensing surface area. Here, copper oxide foam was fabricated using freeze casting. Copper oxide powder was mixed with polyvinyl alcohol in deionized water using stirring and ultrasonication. The dispersed suspension was poured into a silicone mold on a refrigerated Cu rod. At this time, the temperature was maintained at -10 degrees Celsius using liquid nitrogen and a heater. After the suspension was completely frozen, the frozen samples were sublimated in a desiccator at -88 degrees Celsius in vacuum for 40 hours. The green bodies were then reduced from copper oxide (CuO) to copper in a hydrogen atmosphere before sintering. The reduction and sintering process was carried out in a tube furnace under hydrogen gas mixture by pre-sintering at 250 degrees Celsius for 4 hours and high-temperature sintering at 800 degrees Celsius for 14 hours.
[0064] 11A-11G show a schematic process flow for fabricating a metal oxide foam gas sensor device. Platinum electrodes and a ruthenium oxide heater are printed onto a low temperature co-fired ceramic (LTCC) substrate prior to attachment of the metal oxide foam sensor on top of the heater and electrodes using silver paste.
[0065] An example of fabricating a metal oxide sensor electrode device is described in Figures 11A-11G, which show a schematic process flow for fabricating a metal oxide foam gas sensor electrode device. Platinum electrodes and ruthenium oxide heaters are printed onto an LTCC substrate prior to attaching a metal oxide foam sensor in contact with the heater and electrode using silver paste. This sensor device is significantly smaller than, for example, a commercially available sensing module 1203 shown in Figure 12, and is a direct replacement for existing sensing material elements.
[0066] FIG. 12 shows a tin oxide foam sensor device 1212, manufactured as described in this patent, which is a direct replacement for an existing sensing module in a commercially available gas sensor product (eg, a carbon monoxide sensor product).
[0067] This description of the invention has been presented for purposes of illustration and description. It is not intended to be exhaustive or to limit the invention to the precise form described, and many modifications and variations are possible in light of the above teachings. The embodiments have been chosen and described in order to best explain the principles of the invention and its practical application. This description will enable others skilled in the art to best utilize and practice the invention in various embodiments and with various modifications as appropriate for the particular use. The scope of the invention is defined by the following claims.
Claims
1. A gas sensor device, Platinum electrodes and ruthenium oxide heaters printed on a low-temperature co-fired ceramic substrate; a metal oxide foam sensing material; The metal oxide foam sensing material is coupled to the platinum electrodes and the ruthenium oxide heater via silver paste.
2. 10. The device of claim 1, wherein the electrode pattern comprises two electrode pads made of metal spaced a few hundred micrometers apart using a lift-off process and a shadow mask for use as electrodes in the gas sensor device.
3. 10. The apparatus of claim 1, wherein the metal oxide foam sensing material has a porosity between about 55 percent and about 90 percent, is a semiconductor-type gas sensing material in the gas sensor device, and reacts with ethanol, carbon monoxide, oxygen, nitric oxide, hydrogen, or toluene.
4. 4. The device of claim 3, wherein the metal oxide foam sensing material comprises at least one of tin oxide foam or tin oxide foam containing at least one of palladium, gold, silver or platinum catalyst in the range of 0.1 weight percent to 3 weight percent.
5. The metal oxide foam sensing material is tin oxide (SnO or SnO 2 ), zinc oxide (ZnO), indium oxide (In 2 O 3 ), tungsten oxide (WO 3 ), titanium oxide (TiO 2 ), nickel oxide (NiO), copper oxide (CuO), cobalt oxide (Co 3 O 4 ), chromium oxide (Cr 2 O 3 ), and iron oxide (Fe 2 O 3 4. The device of claim 3, wherein the metal oxide is either one or a combination of the metal oxides of
6. A method of making the device of claim 3, comprising the steps of: The method, wherein the manufacturing process for forming the metal oxide foam sensing material includes at least one of freeze casting, space-holding, or dealloying.
7. A method of making the device of claim 3, comprising the steps of: The manufacturing process for forming the metal oxide foam sensing material comprises a freeze casting method followed by a powder slurry preparation and sintering process, in which a water-based or camphene-based oxide powder slurry is frozen and dried at low temperature to form a green body, which is then sintered at high temperature to form a three-dimensionally connected solid porous structure.
8. A method of making the device of claim 3, comprising the steps of: The method, wherein the metal oxide foam sensing material is fabricated via at least one of a thermal oxidation or anodization process on a surface of a metal foam fabricated via at least one of freeze casting, space holder, or dealloying.
9. 10. The method of claim 8, wherein the metal oxide foam sensing material is comprised of at least one of a thin layer of oxide or nanoneedle oxide on the surface of the prepared metal foam.
10. A method of making the device of claim 4, comprising the steps of: The tin oxide foam may contain, in a composition range of about 0.1 weight percent to about 3 weight percent, Li 2 O, CuO, MnO 2 , ZnO, or La 2 O 3 The method according to claim 1, wherein a sintering aid is added to the material.
11. 1. A method for producing metal oxide foams using a freeze casting process, comprising: placing a rectangular insulating silicone mold on a copper or aluminum block immersed in liquid nitrogen, the liquid nitrogen being controlled using a thermocouple and temperature controller, and pouring a metal oxide slurry into the mold, the metal oxide slurry including at least one of deionized water, a dispersant, a binder, a metal or metal oxide powder, and a sintering aid; freezing the slurry such that ice dendrites form and grow in the slurry, with metal oxide particles collecting between the growing ice crystals; drying said ice crystals of the frozen sample at a sufficiently low temperature between about -10 degrees Celsius and about -80 degrees Celsius and at a reduced pressure to form a green metal oxide foam, leaving pores in their original locations; sintering the green metal oxide foam at a sufficiently high temperature between about 800 degrees Celsius and about 1700 degrees Celsius in a controlled furnace under an air or argon atmosphere to form a three-dimensionally connected metal oxide foam having substantial integrity; and machining the metal oxide foam into a rectangular or circular shaped form that is directly applicable as a sensing material in a gas sensor having a ruthenium oxide heater and an underlying platinum electrode.
12. 1. A method of fabricating metal oxide foam for a gas sensor comprising a patterning process for attaching electrode pads in a suitable pattern to the metal oxide foam sensing material, The method, wherein the gas sensor comprises a platinum electrode and a ruthenium oxide heater printed on a low temperature co-fired ceramic substrate, and a metal oxide foam sensing material coupled to the platinum electrode and the ruthenium oxide heater via silver paste.
Citation Information
Patent Citations
Composite metallic oxide body and oxygen sensor
JP1983084124A
sensor
JP1988314452A
Resistive gas detection especially useful for ozone detection
JP1998501623A
Gas sensor
JP2001235442A
Electronic components containing ceramic supports and use of ceramic supports
JP2014505881A